Pengaruh Sistem Akuntansi Manajemen, Kualitas Informasi, dan Ketidakpastian Lingkungan Terhadap Kinerja Manajerial - Adrian Hartanto Darma Sanputra (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
This research aims to examine the influence of management accounting systems, information quality, and business environmental uncertainty on organizational performance at APERSI Association. The research hypotheses posit that management accounting systems, information quality, and business environmental uncertainty significantly affect organizational performance at APERSI Association. The study utilizes primary data in the form of respondent assessments regarding management accounting systems, information quality, business environmental uncertainty, and organizational performance. Data collection methods include questionnaires and literature reviews. The analysis using SMART PLS 4.0. The findings of the research are as follows: (1) management accounting systems have a positive and significant impact on organizational performance; (2) information quality has a positive and significant impact on organizational performance; (3) business environmental uncertainty has a positive and significant impact on organizational performance